1974
DOI: 10.1139/g74-007
|View full text |Cite
|
Sign up to set email alerts
|

INTRASPECIFIC VARIATION OF NUCLEAR DNA CONTENT IN PINUS RESINOSA AIT.

Abstract: Pinus resinosa displays a rather uniform phenotype over a relatively small geographic distribution with a 9-degree latitudinal spread. DNA quantity per cell from 20 seed sources collected throughout the growing range varied significantly by a factor of 2.2 from the lowest to the highest amount. A south-to-north increasing DNA gradient was not observed as reported previously for other members of the Pinaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…On the other hand, some species of Picea and Pinus (Miksche 1968, Dhir and Miksche 1974 and Vicia (Chooi 1971) showed variability in DNA content.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some species of Picea and Pinus (Miksche 1968, Dhir and Miksche 1974 and Vicia (Chooi 1971) showed variability in DNA content.…”
Section: Resultsmentioning
confidence: 99%
“…Bennett and Smith (1971) found neither intraspecific nor interspecific variation in DNA content of diploid species of Hordeum. Intraspecific variation of nuclear DNA content was reported in Picea glauca, P, sitchensis, Pinus banksiana and P. resinosa (Miksche 1968(Miksche , 1971Dhir and Miksche 1974), while in the recent study by Teoh and Rees (1976) such variation was not confirmed in Picea glauca, P. engelmamii and Pinus contorta.…”
Section: Resultsmentioning
confidence: 75%
“…Xiaoxingan in Northeast, China. Chromosome number of this species was 2n=24 in correspondence with other species in the genus Pinus, but there were some reports showing that considerable intraspecific and interspecific variation of nuclear DNA content in this genus (Miksche 1968, 1971, Price et al 1973, Dhir and Miksche 1974, Teoh and Rees 1976, Dhillon 1980, Dhillon et al 1978, Ohri and Khoshoo 1986, Wakamiya et al 1993, Wyman et al 1997. Ohri and Khoshoo (1986) observed that the 20 Pinus species widely collected from North America, Europe and Eurasia had a 1.73-fold variation in nuclear DNA content, and noted that Pinus species with very high DNA content distributed in temperate and highly xeric habitats.…”
mentioning
confidence: 71%
“…The ratio of the highest 1C nuclear DNA content to the lowest 1C nuclear DNA content was 1.36, which was lower than the ratio of 1.5, 1.6, 1.7 and 1.9 respectively among the provenances of Pinus banksiana, Picea glauca, Picea sitchensis and Pseudotsuga menziesii (Miksche 1968, 1971, El-Lakany and Sziklai 1971. Dhir and Miksche (1974) observed that the maximum ratio was 2.2 of North red pine (Pinus resinosa) distributed in relatively small geographical distribution. Price (1988) considered that difference in total nuclear content was in range of 5-10%, it was sufficient to be subject to selection.…”
Section: Resultsmentioning
confidence: 99%